MEMBANGUN KESADARAN PENTINGNYA SENSORY PLAY UNTUK KETERAMPILAN DAN KEMAMPUAN KOGNITIF ANAK MELALUI PENYULUHAN DI POSYANDU RAJAWALI KOTA SERANG - Jamaludin, Ujang; Cahya Ningrum, Rafika; Karima Fasya, Nada; Puji Lestari, Nathalia; Pitriah; Dwi Wulandari, Putri; Mulyanah; Aeni, Nurul; Sulistiawati, Putri; Faisal, Putri; Widiastuti Wijaya, Putri; Ramadhan, Mutiara; Evasufi Widi Fajari, Laksmi (Jurnal Abdimas Bina Bangsa, 2024)
This community service aims to improve the knowledge and skills of Posyandu cadres in stimulating the motor and sensory development of early childhood, especially during the golden period of development (age 0-6 years). This activity was carried out at Posyandu Rajawali, Kp. Dukuh Pinang, Baros, Serang Regency, involving 10 active Posyandu cadres. The methods applied in this program include counseling and training carried out for three consecutive meetings. The results of the activity showed that 80% of participants stated that this program was very good and provided significant benefits. The level of participant satisfaction was also quite high, with 40% stating that they were very satisfied, 50% satisfied, and only 10% feeling less satisfied. This program has proven effective in improving the competence and expertise of Posyandu cadres in supporting and stimulating the motor and sensory development of children at an early age. It is hoped that with the increased knowledge and skills obtained, Posyandu cadres can contribute more optimally in monitoring, stimulating, and supporting the development of early childhood in their environment.